2008
DOI: 10.1186/cc6212
|View full text |Cite
|
Sign up to set email alerts
|

Bench-to-bedside review: Candida infections in the intensive care unit

Abstract: Invasive mycoses are life-threatening opportunistic infections and have emerged as a major cause of morbidity and mortality in critically ill patients. This review focuses on recent advances in our understanding of the epidemiology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
147
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(161 citation statements)
references
References 99 publications
6
147
0
8
Order By: Relevance
“…Bu türler, Amerika Birleşik Devletleri (ABD) ve Avrupa'da sırasıyla dördüncü ve altıncı en yaygın hastane kökenli kan dolaşımı enfeksiyonu etkenidir 2,3 . Türkiye'de ise Candida türleri kan dolaşımı enfeksiyonlarının üçüncü en yaygın nedeni (%10.1) olarak bildirilmektedir 4 .…”
Section: Introductionunclassified
“…Bu türler, Amerika Birleşik Devletleri (ABD) ve Avrupa'da sırasıyla dördüncü ve altıncı en yaygın hastane kökenli kan dolaşımı enfeksiyonu etkenidir 2,3 . Türkiye'de ise Candida türleri kan dolaşımı enfeksiyonlarının üçüncü en yaygın nedeni (%10.1) olarak bildirilmektedir 4 .…”
Section: Introductionunclassified
“…Although the dynamics of colonization assessed semiquantitatively by the colonization index has been shown to predict the risk of IC, this information is lacking in the present study [8,9,12]. Simultaneous sampling of blood cultures from a catheter line and by peripheral venipuncture is recommended.…”
mentioning
confidence: 96%
“…Pending the conclusion on ongoing investigations and on the role of composite clinical scores which may improve the prediction of IC, therapeutic decisions remain essentially based on the clinical risk profile [7]. This approach results in a low threshold for starting antifungals (prophylactic, pre-emptive or empirical treatment) and in a high number needed to treat to target a single IC episode [8,9].…”
mentioning
confidence: 99%
“…In different studies around the globe [5,[15][16][17][18] and in India, [6,9,[19][20][21][22][23] it was observed that, NCA species were predominant (30-90%) among the isolated Candida species. Some authors have attributed this emergence of NCA species to the prophylactic use of fluconazole, in the species distribution of Candida, but it is not the factor in our study.…”
Section: Discussionmentioning
confidence: 99%